Factors contributing to misallocation of RDP-Low cost houses to beneficiaries at Namakgale in Mopani District of Limpopo Province - Malatji, M.P. (University of Limpopo (Turfloop Campus), 2011)
Refer to document
Thesis (MPA.) --University of Limpopo, 2011
Keywords: Houses; Beneficiaries; Reconstruction and Development Programme (RDP); 363.5; Housing, Rural; Housing subsidies -- South Africa -- Limpopo